KORELASI KEKUATAN GENGGAMAN TANGAN DENGAN KARAKTER ANTROPOMETRI LENGAN BAWAH DAN TANGAN SERTA INDEKS MASSA TUBUH - Heidy Heidy; Tena Djuartina; Robi Irawan (Atma Jaya Catholic University of Indonesia, 2019)
Introduction: An individual’s overall muscle strength is commonly assessed by a power grip measurement, a reliable indicator of functional capacity and physical condition. The development of muscle parallels the changes of body composition during growth. Aim of this study is to examine the correlationship between hand grip strength and anthropometric. Methods: This cross-sectional study involved 76 male students of Dhammasavana School, aged between 12 – 16 years old, North Jakarta. Hand grip strength was examined using a digital dynamometer on the dominant side. Statistical analysis was computed using SPSS ver. 15.0 program with Spearman correlations test. Significance was set at p<0.05. Results: Dominant hand grip strength was found to have significant (p<0.05 - 0.001) positive correlation with height (r=0.612), lower arm muscle-and-bone cross-sectional circumference and area (CSA) (r=0.553 and r=0.553 respectively), hand length (r=0.548), forearm length (r=0.540), age (r=0.520), weight (r=0.416), and forearm girth (r=0.376). Conclusion: No significant correlation between grip strength and body mass index was found. Positive correlations between the variables mentioned above conclude that the higher the value of the anthropometric measurements, the greater the strength generated in a power grip.